Education in Physics for Rural Children - Singh, Surjeet (SCHOOL SCIENCE, 2013)
First, we note that our target is rural children. We shall look at the deficiencies of physics curriculum planning which I had experienced as an administrator. Then we shall make a few assumptions for designing a physics course for the school children of rural areas. But before these postulates, we must look into the rural conditions as prevalent today. And also, what is physics? The last question appears ridiculous? Who does not know that physics is a study of matter, energy and the effects of energy on matter. I recall the topic being discussed is ’physics education in rural areas’. The word ’physics’ qualifies the noun ’education’. I think that there are three features of physics. One, the content of physics by which I mean facts, concepts, principles, models, i.e., hypotheses, equations relating different physical quantities. These equations represent the epitome of experiences over centuries. We can describe facts by observation, check them by experiments, i.e., acquiring information, and explain them by a theory. The second feature is the method of physics. No one method is known to us. B